An ultrahigh vacuum system for the scattering of keV ions by a clean silicon(100) surface. - Bruyère, Michel Jean. (University of Ottawa (Canada), 1990)
An ultrahigh vacuum surface physics system was designed and built to study ion-surface interactions at various incident angles by detection of the forward scattered particles. The proposed initial measurement is the scattering of keV ions by a clean Si(100) surface.
Keywords: Physics, Condensed Matter.